2020
DOI: 10.1038/s41598-020-70717-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel nomogram model for differentiating Kawasaki disease from sepsis

Abstract: Kawasaki disease (KD) is a form of systemic vasculitis that occurs in children under the age of 5 years old. Due to prolonged fever and elevated inflammatory markers that are found in both KD and sepsis, the treatment approach differs for each. We enrolled a total of 420 children (227 KD and 193 sepsis) in this study. Logistic regression and a nomogram model were used to analyze the laboratory markers. We randomly selected 247 children as the training modeling group and 173 as the validation group. After compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
(35 reference statements)
1
14
1
Order By: Relevance
“…In the present study, we compared serum level of PCT among acute KD patients, sepsis patients and the healthy controls, and found that it experienced the highest increase in sepsis patients before antibiotic therapy, followed by acute KD patients and the healthy controls. Consistently, two controlled clinical trials from Chongqing and Guangdong, China [18,19], indicated that serum PCT in acute KD patients had a signi cant increase compared with the healthy controls (1.4 ng/ml vs 0.2 ng/ml), whereas was signi cantly lower than that in sepsis patients (1.4 ng/ml vs 4.1 ng/ml). Based on these current evidence, serum PCT in acute KD patients is almost 7-20 folds higher above baseline, whereas 3-5 folds lower than that in sepsis patients.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In the present study, we compared serum level of PCT among acute KD patients, sepsis patients and the healthy controls, and found that it experienced the highest increase in sepsis patients before antibiotic therapy, followed by acute KD patients and the healthy controls. Consistently, two controlled clinical trials from Chongqing and Guangdong, China [18,19], indicated that serum PCT in acute KD patients had a signi cant increase compared with the healthy controls (1.4 ng/ml vs 0.2 ng/ml), whereas was signi cantly lower than that in sepsis patients (1.4 ng/ml vs 4.1 ng/ml). Based on these current evidence, serum PCT in acute KD patients is almost 7-20 folds higher above baseline, whereas 3-5 folds lower than that in sepsis patients.…”
Section: Discussionmentioning
confidence: 67%
“…Based on this nding, PCT concentrations below 0.25 ng/ml may be useful for discriminating KD from sepsis. Recently, Liu et al [19] developed a novel nomogram model to differentiate KD from sepsis, in which PCT ≤ 0.5 ng/ml was regarded as a strong predictor for KD with 57 points, and associated with a 3.41-fold increase in KD probability. However, in a retrospective study encompassing 49 KD patients and 24 sepsis patients from Korea, Lee et al [22] divided both KD and sepsis patients into <0.25 ng/ml group, 0.25-1.0 ng/ml group and >1.0 ng/ml group based on PCT concentrations, and found that PCT was not helpful for discriminating KD from sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we compared serum level of PCT among acute KD patients, sepsis patients and the healthy controls and found that it experienced the highest increase in sepsis patients before antibiotic therapy, followed by acute KD patients and the healthy controls. Consistently, two controlled clinical trials from Chongqing and Guangdong, China [ 20 , 21 ], indicated that serum PCT in acute KD patients had a significant increase compared with the healthy controls (1.4 ng/ml vs 0.2 ng/ml), whereas it was significantly lower than that in sepsis patients (1.4 ng/ml vs 4.1 ng/ml). Based on these current evidence, serum PCT in acute KD patients is almost 7–20 folds higher above baseline, whereas 3–5 folds lower than that in sepsis patients.…”
Section: Discussionmentioning
confidence: 69%
“…Recently, Liu et al . [ 21 ] have developed a novel nomogram model to differentiate KD from sepsis, in which PCT ≤ 0.5 ng/ml was regarded as a strong predictor for KD with 57 points, and associated with a 3.41-fold increase in KD probability. However, in a retrospective study encompassing 49 KD patients and 24 sepsis patients from Korea, Lee et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation